UPAYA PENINGKATAN KEMAMPUAN GURU DALAM MENGUASAI MODEL PEMBELAJARAN AKTIF DI MTs NEGERI 3 MAGELANG TAHUN PELAJARAN 2021/2022 - Hartsa Jamila Rochi; Priyastiwi Priyastiwi (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
This research use desciptive qualitative approach. The informants in this study were 7 resource persons, namely 1 Madrasah Principal, 1 Deputy Head of Madrasah, 2 teachers, and 3 students of MTs N 3 Magelang. Data analysis is to follow the path stated by Miles and Huberman in Sugiyono (2010:124) that data analysis consists of three streams of activities that occur simultaneously, namely data reduction, data exposure/presentation and drawing conclusions. As a result, the efforts made to improve the ability of teachers in active learning at MTs Negeri 3 Magelang for the 2021/2022 academic year which consists of (a) Learning Program Planning is improved by planning for classroom management, planning for organizing materials, planning for the management of active teaching and learning activities (b) Teaching and Learning Activities (Learning Process) are improved with the teacher efforts, it is recommended to improve IT skills and in accordance with learning objectives (c) Evaluation/assessment of learning is improved by further enhancing the ability to conduct assessments during teaching and learning activities.